Measuring the vertical specialization in Chinese trade - Judith Dean; K. C. Fung; Zhi Wang (University of California, Santa Cruz Institute for International Economics (SCIIE), 2008)
In recent years, two important related developments have transformed the nature of world trade: the explosive growth of Chinese trade, and the growth of vertically specialized trade due to international production fragmentation. The literature in each of these two separate topics is large and growing. However, very few papers quantitatively assess these two trends together. In this paper, we measure the degree to which Chinese trade has become vertically specialized, using a new measure adapted from Hummels, Ishii and Yi (2001). By making use of the latest Chinese input-output tables, and a new detailed Chinese trade dataset which distinguishes processing trade from other forms of trade, we develop a new method of identifying intermediate goods imported into China. With this new method, we measure Chinese vertical specialization over time, and by sector, export destination, and input source. We find about 35 percent of the value of China's exports to the world is attributable to imported inputs. This vertical specialization exceeds 50% in some sectors, and is growing over time.
Keywords: F10; F14; 330; China; fragmentation; vertical specialization; trade growth; Internationale Arbeitsteilung; Vorprodukt; Auslandsverlagerung; Input-Output; China